2020
DOI: 10.30738/natural.v7i1.8117
|View full text |Cite
|
Sign up to set email alerts
|

Bagaimana perbandingan kurikulum 2013 dengan kurikulum Australia pada mata pelajaran IPA?

Abstract: This is an open access article under the CC-BY-SA license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…The curriculum is defined as a set of subjects, educational programs, and learning designs given to students. The curriculum in Indonesia is defined as a set of educational plans to keep up with society's dynamic demands (Wicaksono & Sayekti, 2020). The national curriculum is designed based on Pancasila and the 1945 Constitution.…”
Section: Discussionmentioning
confidence: 99%
“…The curriculum is defined as a set of subjects, educational programs, and learning designs given to students. The curriculum in Indonesia is defined as a set of educational plans to keep up with society's dynamic demands (Wicaksono & Sayekti, 2020). The national curriculum is designed based on Pancasila and the 1945 Constitution.…”
Section: Discussionmentioning
confidence: 99%
“…The new integration can only be seen in the layer-by-layer combination of physics, chemistry, and biology. The overall integration perspective is not mentioned (Michie, 2019;Wicaksono & Sayekti, 2020). This is in line with science which studies comprehensively objects from phenomena and natural phenomena.…”
Section: Introductionmentioning
confidence: 98%
“…Educators take control as a facilitator and control the process of learning. Science learning is one of the educational problems in Indonesia (Wicaksono & Sayekti, 2020;Yusuf, 2018). A study conducted by the Organization for Economic Co-Operation and Development (OECD) surveyed the program for International Student Assessment (PISA) ) and showed that from 2009 to 2018 Indonesia was ranked 10th from the bottom.…”
Section: Introductionmentioning
confidence: 99%
“…Trends in Students Achievement in Mathematics and Science (TIMSS) also show that Indonesia is ranked 5th from the bottom from 2011 to 2015 (Nugrahanto & Zuchdi, 2019;Suryana et al, 2022). The survey results illustrate that Indonesian education needs improvement (Pratiwi, 2019;Wicaksono & Sayekti, 2020). The implementation of the national education system was considered unsuccessful so the Indonesian government was under public pressure, it is based on the results of the PISA assessment since 2000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation